Bone and Mineral Disorder in Renal Transplant Patients: Overview of Pathology, Clinical, and Therapeutic Aspects - Molinari, Paolo; Alfieri, Carlo Maria; Mattinzoli, Deborah; Campise, Mariarosaria; Cervesato, Angela; Malvica, Silvia; Favi, Evaldo; Messa, Piergiorgio; Castellano, Giuseppe (Frontiers in Medicine, 2022)
Renal transplantation (RTx) allows us to obtain the resolution of the uremic status but frequently is not able to solve all the metabolic complications present during end stage renal disease. Mineral and bone disorders (MBD) are frequent since the early stages of chronic kidney disease (CKD) and strongly influence the morbility and mortality of CKD patients. Some mineral metabolism (MM) alterations can persist in RTx patients (RTx-p), also in the presence of complete renal function recovery. In those patients, anomalies of Calcium, Phosphorus, Parathormone, fibroblast growth factor 23 and Vitamin D such as of bone and vessels are frequent and related both to pre-RTx and post-RTx specific factors. Actually, many treatments are present for the management of post-RTx MDB. Despite that, guidelines able to give clear directives in MBD treatment of RTx-p are still missed. For the future, with the aim of obtaining an ever-greater individualization of therapy, an increase of the evidence and the specificity of international guidelines and a more uniform management of these anomalies worldwide should be expected. In this review the major factors related to post-renal transplant MBD (post RTx-MBD), the main mineral metabolism biochemical anomalies and the principal treatment for post-RTx MBD will be reported.